2020
DOI: 10.1155/2020/8845133
|View full text |Cite
|
Sign up to set email alerts
|

PredAmyl-MLP: Prediction of Amyloid Proteins Using Multilayer Perceptron

Abstract: Amyloid is generally an aggregate of insoluble fibrin; its abnormal deposition is the pathogenic mechanism of various diseases, such as Alzheimer’s disease and type II diabetes. Therefore, accurately identifying amyloid is necessary to understand its role in pathology. We proposed a machine learning-based prediction model called PredAmyl-MLP, which consists of the following three steps: feature extraction, feature selection, and classification. In the step of feature extraction, seven feature extraction algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 104 publications
0
25
0
Order By: Relevance
“…The Amy dataset constructed by Niu et al 20 had previously been used to train and develop the four existing state-of-the-art methods (RFAmyloid 20 , iAMY-SCM 21 , PredAmyl-MLP 22 and Mukhtar et al’s method 23 ). The Amy dataset was used as the benchmark dataset to compare the performance of the proposed method to the four existing state-of-the-art methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Amy dataset constructed by Niu et al 20 had previously been used to train and develop the four existing state-of-the-art methods (RFAmyloid 20 , iAMY-SCM 21 , PredAmyl-MLP 22 and Mukhtar et al’s method 23 ). The Amy dataset was used as the benchmark dataset to compare the performance of the proposed method to the four existing state-of-the-art methods.…”
Section: Methodsmentioning
confidence: 99%
“…According to the findings of Charoenkwan et al 21 , iAMY-SCM performed at a comparable level to that of RFAmyloid, as evaluated via cross-validation and independent testing. Most recently, Li et al 22 and Mukhtar et al 23 used amino acid composition (AAC), tripeptide composition (TPC), physicochemical properties of amino acids (AAI), secondary structure-based alignments, and the segmented-position specific scoring matrix (PSSM) method to improve predictive performance. The computational approaches mentioned above each had their own merits and sparked interest in amyloid protein identification research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tripeptide composition (TPC) method describes the position and order information of amino acids in a sequence [ 48 , 49 ]. Li et al [ 50 ] have confirmed that the TPC feature is beneficial for classifying amyloid proteins, and therefore we considered their utilization in the investigation of amyloidogenic regions. In this method, the occurrence frequencies of three consecutive amino acids in the sequence are used as the feature elements.…”
Section: Methodsmentioning
confidence: 99%
“…This method can extract a total of 188 feature dimensions, so it is also called 188D ( Li et al, 2020b ). The 188D top 20 extraction dimension vectors were used to calculate the frequency of the arrangement for 20 kinds of natural amino acids (A, C, D, E, F, G, H, I, K, L, M, N, P, Q, R, S, T, V, W, Y) ( Zheng et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%